2017
DOI: 10.1093/jme/tjx172
|View full text |Cite
|
Sign up to set email alerts
|

Two New Species and Seven New Records of Horse Fly (Diptera: Tabanidae) From Malaysia, Including a Description of New Species and Modified Keys

Abstract: Horse flies (Diptera: Tabanidae) are of medical and veterinary importance, as their blood-sucking feeding habit enables them to transmit several disease-causing agents. In Malaysia, the family Tabanidae consists of 120 species belonging to eight genera. The current study describes two new species (Chrysops idlani sp. nov. and Tabanus ekor sp. nov.) and presents new records for seven species: Tabanus fontinalisSchuurmans Stekhoven, 1926; Tabanus fuscifronsSchuurmans Stekhoven, 1926, Tabanus latifasciesSchuurman… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 9 publications
1
5
0
Order By: Relevance
“…Hamon et al in 1956 [31], Ovazza in 1967 [30] and Raymond et al in 1980 [22] reported in separate works their existence in Senegal. The description of specimens at the species level performed in our study was consistent with that of Ricardo [4] and Crosskey [28] for T. guineensis, Mugasa et al [7] for C. distingutipennis and Baldacchino et al [2] and Hamon et al [31] and Al-Talatha et al [1] for A. fuscipes.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Hamon et al in 1956 [31], Ovazza in 1967 [30] and Raymond et al in 1980 [22] reported in separate works their existence in Senegal. The description of specimens at the species level performed in our study was consistent with that of Ricardo [4] and Crosskey [28] for T. guineensis, Mugasa et al [7] for C. distingutipennis and Baldacchino et al [2] and Hamon et al [31] and Al-Talatha et al [1] for A. fuscipes.…”
Section: Discussionsupporting
confidence: 89%
“…Male insects feed on nectar and do not present medical interest. In contrast, female tabanids of most species are haematophagous, being able to obtain large stores of blood from their hosts by telmophagy [1,2]. These arthropods are considered to be primarily mechanical vectors of various human and animal pathogens, including bacteria, viruses, helminths, and protozoans [2,6,7].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations